EFEKTIVITAS BIOREMEDIASI MENGGUNAKAN BAKTERI Pseudomonas UNTUK MENURUNKAN KADAR COD LIMBAH ORGANIK DI PABRIK CINCAU KOTA MEDAN - Safitri, Dian; Reulina, Yohana; Sebayang, Agnes; Pinaring, Nabila; Nilan Sari, Marlinda; Febriyosa, Adelia (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Background: Environmental pollution, especially due to organic waste from the food industry, is a serious problem in today's society. Waste from grass jelly factories contains high organic content which causes an increase in Chemical Oxygen Demand (COD) and has the potential to pollute water and ecosystems. This study aims to evaluate the effectiveness of Pseudomonas bacteria as a bioremediation agent in reducing COD levels in grass jelly factory waste. Methods: The methods used consisted of observational and experimental, with testing carried out at the Microbiology Laboratory, State University of Medan. Results: The results showed that after 14 days of treatment, COD levels decreased from 195.75 mg/L to 154.73 mg/L, indicating a decrease of around 20.9%. Conclusion: This study concludes that Pseudomonas bacteria are effective in reducing organic pollution in grass jelly factory waste, so they have the potential to be applied in industrial waste management.